Turbotronik – On the Border between the Local Music Scene and a Genre in the Making - Banić Grubišić, Ana; Kulenović, Nina (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2019)
This paper shows preliminary results from an ethnographic study of the modern musical phenomena that gathers “authors from the Serbian scene”, who’s creations are based on the mixture of the newly composed folk music and turbo-folk, along with various alternative music genres and styles. The research is conducted through the technique of semi-structured interviews with the artists and event organizers, as well as attending different events (concerts, compilation promotion, festivals Zasram and FESRAM), and using written and audiovisual materials that are accessible on the Internet. One of the main aims of this study is to designate the form of “turbotronik” phenomena in the context of music genre and scene, as well as recognizing its local characteristics. Through the analysis of different processes that influence the formatting of a specific music genre (name of the genre, the narrative on genre origin, visual identity, specific sound, the thematic of the songs and characteristics of the genre’s public) “turbotronik” is being observed as sort of a “genre in the making”.